Drip, drop - Weeks, Sarah; Manning, Jane (New York : HarperCollins, 2000)
Pip Squeak the mouse is kept awake all night by the drips from his leaky roof.
School Library Journal, September 2000
Booklist, July 2000
Keywords: Mice -- Fiction; Rain and rainfall -- Fiction; Stories in rhyme; Mice -- Fiction; Rain and rainfall -- Fiction; Stories in rhyme